Manifestations of intertextuality in the poetry collection *“Gates of Light”* by Abdelkader Ben Mohamed Ben El-Kadhi - slimani, hakim (El Omda in Linguistics and Discourse Analysis, 2022)
The poetic text is a world open to previous or contemporary texts, whether literary or non-literary. Therefore, this article is known as the Algerian poet Abdelkader bin Muhammad bin al-Qadi and his collection poetry “Gates of Light” ;researches his poetry, and attempts to reveal the manifestations of his openness to previous texts and contemporary texts. We have decided to arrange the subject by looking at the absent texts that he brought up represented in the Holy Qur’an, then ancient and modern Arabic poetry.